The influence of social demographic factor and student’s academic achievement towards Obsessive Compulsive Disorder (OCD) status among students in UiTM (Kelantan) Kampus Kota Bharu / Wan Nur Atiqah Wan Habib, Wan Syakirah Wan Jamil and Siti Akmar Sa’mah - Wan Habib, Wan Nur Atiqah; Wan Jamil, Wan Syakirah; Sa’mah, Siti Akmar (2017)
Obsessive Compulsive Disorder (OCD) was defined by repeated and unpleasant feelings, images or desires (obsessions) and repetitive action or mental acts (compulsions).The study was conducted to determine the influence of social demographic factor and student’s academic achievement towards Obsessvie Compusive Disorder (OCD) status among students in UiTM (Kelantan) Kampus Kota Bharu. There are three social demographic factors which are gender, family history and relationship status and two level of student’s academic achievement (dean, not dean) and status of Obsessive Compulsive Disorder (OCD) (yes and no). A cross-sectional study of OCD was conducted among students in UiTM (Kelantan) Kampus Kota Bharu. The validated self-administrated questionnaire was distributed to 314 students who were selected by using a proportionate stratified random sampling technique. This study use Yale-Brown Obsessive Compulsive Disorder Scale to measure the status of obsessive compulive disorder. Chi-square test and Multiple Binary Logistic Regression were used for data analysis. The overall prevalence of OCD among students in UiTM (Kelantan) Kampus Kota Bharu were male students, the students who have family history of OCD, the students who are not in relationship and the students who did not get dean. Factors associated with OCD status were gender, family history, relationship status and students academic achievement. By using Multiple Binary Logistic Regression, it was found that there are one variable that not significantly influence towards OCD Status which is gender since the p-value was more than 0.05. However, there are three variables which are family history, relationship status, and CGPA category are significantly influence towards Obsessive Compulsive Disorder Status since the p-value for Binary Logistic Regression was less than 0.05 (p-value: 0.001, 0.001, 0.002). The prevalence of students who have OCD were low compare to students who did not have OCD. Thus, appropriated action to control it before it getting worse were suggested for students who have OCD